2020
DOI: 10.3389/fmicb.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Scent of a Killer: Microbial Volatilome and Its Role in the Biological Control of Plant Pathogens

Abstract: The use of synthetic fungicides represents the most common strategy to control plant pathogens. Excessive and/or long-term distribution of chemicals is responsible for increased levels of environmental pollution, as well as adverse health consequence to humans and animals. These issues are deeply influencing public perception, as reflected by the increasing demand for safer and eco-friendly agricultural commodities and their by-products. A steadily increasing number of research efforts is now devoted to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 124 publications
(179 reference statements)
1
101
0
3
Order By: Relevance
“…It was revealed that some Aureobasidium species demonstrated biological control activity against phytopathogens, such as Botrytis, Bacillus, Colletotrichum, Penicillium [43,52,53]. The antagonistic activity of A. pullulans mainly includes nutrient competition and production of volatile organic compounds or glucanases, chitinases, and extracellular proteases [40,46]. Taphrina and Cladosporium were the next numerous fungal microorganisms observed on unripe sea buckthorn berries in our study (Table S1, Figure 2).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…It was revealed that some Aureobasidium species demonstrated biological control activity against phytopathogens, such as Botrytis, Bacillus, Colletotrichum, Penicillium [43,52,53]. The antagonistic activity of A. pullulans mainly includes nutrient competition and production of volatile organic compounds or glucanases, chitinases, and extracellular proteases [40,46]. Taphrina and Cladosporium were the next numerous fungal microorganisms observed on unripe sea buckthorn berries in our study (Table S1, Figure 2).…”
Section: Discussionmentioning
confidence: 62%
“…Various microorganisms act as biological control agents of phytopathogens and have a role in postharvest decay and toxin contamination by emitting volatile organic compounds [40,43]. Several biocontrol yeasts (e.g., Candida oleophila, Aureobasidium pullulans, Metschnikowia fructicola, Cryptococcus albidus, Saccharomyces cerevisiae) have already been used for the production of commercial plant protection products, encouraging the deeper exploration of the fascinating traits and application possibilities of other yeasts as well [16,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations